2005
DOI: 10.1292/jvms.67.735
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuppurative Myocarditis Caused by Porcine Circovirus Type 2 in a Weak-Born Piglet

Abstract: ABSTRACT. Reproductive failure associated with porcine circovirus type 2 (PCV2) was observed in a farm, and a weak-born 8-day-old piglet was examined pathologically. Focal to locally extensive lesions, including infiltration of macrophages and lymphocytes, fibrosis and degeneration of the myocardium were observed in the heart. PCV2 antigens and nucleic acids were detected in degenerated cardiomyocytes and macrophages infiltrating the heart by immunohistochemical staining and in situ hybridization. Depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
6
24
0
Order By: Relevance
“…Similar pathomorphological changes as found in our study are described in several other works (Mikami et al 2005, Segales et al 2005, Martinez et al 2006, Brunborg et al 2007, Phaneuf 2007.…”
Section: Discussionsupporting
confidence: 92%
“…Similar pathomorphological changes as found in our study are described in several other works (Mikami et al 2005, Segales et al 2005, Martinez et al 2006, Brunborg et al 2007, Phaneuf 2007.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of interstitial pneumonia in preweaned piglets infected with PCV2 corroborated earlier observations made in experimentally induced PCV2 infection (Pallares et al, 2002). The heart lesions were less severe than those described previously (Mikami et al, 2005;O'Connor et al, 2001;West et al, 1999) however, our findings supported the earlier observations made by these authors that the cardiovascular system in general and endothelial cells in particular plays an important role in the pathogenesis of PCV2-associated diseases. The lesions in liver, kidneys, spleen and lymph nodes were similar to previous observations in weaner pigs diagnosed with PMWS (PerezMartin et al, 2007;Rovira et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…8) is the hallmark lesion in stillborn and neonatal pigs from field cases. 91 Experimental intrauterine infection of fetuses with PCV2 resulted in virus replication in the fetuses and supports the heart as the primary site of PCV2 replication in fetuses. 122 When fetuses were inoculated in utero on 57, 75, and 92 days of gestation, it was found that virus replication was significantly higher in fetuses inoculated at 57 days of gestation compared to those inoculated at 75 and 92 days of gestation.…”
Section: Pcv2-associated Reproductive Failurementioning
confidence: 84%